User manual for mapping Member State zoonoses standard terminology to EFSA standard terminology for information derived from the year 2017. Issue 1 (31st January 2018) - ,; Mulligan, Kenneth; Stoicescu, Anca‐Violeta
Abstract : This publication is linked to the following EFSA Supporting Publications articles: http://onlinelibrary.wiley.com/doi/10.2903/sp.efsa.2018.EN-1368/full, http://onlinelibrary.wiley.com/doi/10.2903/sp.efsa.2018.EN-1369/full, http://onlinelibrary.wiley.com/doi/10.2903/sp.efsa.2018.EN-1370/full